EFFECT OF NITROGEN AND ZINC APPLICATION ON MORPHOLOGICAL PARAMETERS AND YIELD ATTRIBUTES IN PADDY (Oryza sativa L.) - K. SUPRIYA, B. V. NAGESHA , RAMESH THATIKUNTA, S. NARENDER REDDY, L. KRISHNA and (The Journal of Research, PJTSAU, 2020)
In India, rice is grown in an area of 44.5 M ha with a production 115.60 Mt and a productivity of 2800 kg ha-1. Telangana State contributes 2.09 million ha area annually with a production of 6.62 million tonnes, with an average productivity of 3295 kg ha-1 during 2018-2019 (CMIE, 2019). The input of nitrogenous fertilizers is closely related to the increase in yield which is a consequence of the increased photosynthetic capacity of the leaves, formation of tillers, differentiation of spikelets and quality of grains (Tanaka et al., 2012). Farmers have the habit of application of excess fertilizers to seek more yield. However, excess application of nitrogen can lead to detrimental impacts such as crop lodging, delay in ripening, poor grain yield and quality (Zhang et al., 2014). Excess N leads to low N use efficiency,enormous N losses, high production cost and environmental pollution (Peng et al., 2006; Qiao et al., 2013).